2017
DOI: 10.1177/0899764017728365
|View full text |Cite
|
Sign up to set email alerts
|

What Regulation, Who Pays? Public Attitudes to Charity Regulation in England and Wales

Abstract: Funding for England and Wales’ Charity Commission has been cut by 48% between 2007 and 2016, affecting its ability to deliver its core regulatory functions. Conversations around what charity regulation should look like and how it should be funded have, therefore, gained momentum. These debates, however, are not limited to England and Wales, and in this article, we contribute to them by exploring public attitudes to these questions, presenting the findings of four focus groups. We find that although public know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Finally, the investigations data utilised in this study should not be considered as a complete record of dissatisfaction and misconduct in the sector. Many actors may be unwilling to raise their concerns with the regulator: for example, they may be unaware of to whom the complaint should be directed to or fearful of repercussions should they lodge their complaint (see Hogg, 2016). Rothschild's (2013) study of misconduct reporting in the charity sector posits that whistle-blowers observe misconduct several times before reporting this behaviour; the same study also found that whistle-blowers were subject to retaliation by the organization in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the investigations data utilised in this study should not be considered as a complete record of dissatisfaction and misconduct in the sector. Many actors may be unwilling to raise their concerns with the regulator: for example, they may be unaware of to whom the complaint should be directed to or fearful of repercussions should they lodge their complaint (see Hogg, 2016). Rothschild's (2013) study of misconduct reporting in the charity sector posits that whistle-blowers observe misconduct several times before reporting this behaviour; the same study also found that whistle-blowers were subject to retaliation by the organization in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Regulations that curb the power of philanthropic organizations to commit fraud ensures that only legitimate and trustworthy organizations solicit donations. On the one hand, this enables individuals to donate while reducing their transaction costs related to monitoring the quality of organizations (Hogg, 2017). On the other hand, these and other regulations can increase costs for the establishment and operation of philanthropic organizations, reducing giving (Huck & Rasul, 2010;Knowles & Servátka, 2015).…”
Section: Regulations and Fiscal Incentives: Formal-public Institutionmentioning
confidence: 99%
“…Trust can be considered both at a sector (where charity regulation breeds confidence: E. Hogg, 2018) and also at an individual charity level. Bekkers (2003) notes that trust (often assessed through formal accreditations or testimonies) correlates significantly with giving.…”
Section: Trustmentioning
confidence: 99%